1988
DOI: 10.1021/bi00423a011
|View full text |Cite
|
Sign up to set email alerts
|

CP4: a pneumocyte-derived collagenous surfactant-associated protein. Evidence for heterogeneity of collagenous surfactant proteins

Abstract: Type II pneumocytes secrete pulmonary surfactant and are known to synthesize SP-35, a collagenous surfactant-associated protein. Freshly isolated type II cells also synthesize other bacterial collagenase-sensitive and hydroxyproline-containing proteins, including a glycoprotein designated CP4. CP4 was isolated from rat pneumocyte culture medium by immune precipitation with polyclonal antibodies to rat surfactant proteins or by DEAE chromatography and reverse-phase or gel permeation HPLC. CP4 did not cross-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…3 is one of the collectins, a family of oligomeric proteins whose individual chains consist of a collagen region linked to a C-type lectin domain via an ␣ helical neck region (1,2). The structural subunits of SP-D are homotrimers of these chains, and the subunits are themselves oligomerized into cross-like tetramers and higher oligomers (3)(4)(5)(6)(7)(8).…”
Section: Ung Surfactant Protein D (Sp-d)mentioning
confidence: 99%
“…3 is one of the collectins, a family of oligomeric proteins whose individual chains consist of a collagen region linked to a C-type lectin domain via an ␣ helical neck region (1,2). The structural subunits of SP-D are homotrimers of these chains, and the subunits are themselves oligomerized into cross-like tetramers and higher oligomers (3)(4)(5)(6)(7)(8).…”
Section: Ung Surfactant Protein D (Sp-d)mentioning
confidence: 99%
“…C-type lectins bind, in a calcium-dependent manner, to targets presenting ligands with adequately spaced terminal carbohydrate groups (1). Although the first collectin identified, conglutinin, was reported 100 years ago (2), the study of collectins only took broader interest with the identification in 1978 of mannan-binding lectin (MBL) (3), followed by surfactant protein A (4) and surfactant protein D (5). Three further collectins were more recently discovered by Wakamiya and co-workers, i.e.…”
mentioning
confidence: 99%
“…The serum SP-D level and mutation status were not related with overall survival in the extension study (data not shown). SP-D is the specific glycoprotein produced and secreted by normal alveolar type II cells and Clara cells, and it is responsible for the production of pulmonary surfactant protein [13,14]. Most SP-D can be both broken down by pulmonary macrophages and reabsorbed into the lamellar structures of type II cells as the pulmonary surfactant protein, while the remainder of it is transferred into the circulating blood; serum SP-D is well known as a marker of activity of interstitial lung diseases [18,19].…”
Section: Extension Study Of Egfr Mutationsmentioning
confidence: 99%